Steering protein and lipid digestibility by oleogelation with protein aerogels. Issue 20 (28th September 2022) - Plazzotta, Stella; Alongi, Marilisa; De Berardinis, Lorenzo; Melchior, Sofia; Calligaris, Sonia; Manzocco, Lara
Abstract : The destructuring behaviour during gastrointestinal digestion of oleogels obtained through the whey protein aerogel-template approach modulates both lipid and protein digestibility. Abstract : The aim of the present work was to assess the effect of an innovative oleogelation strategy, the aerogel-template approach, on protein and lipid digestibility. Whey protein isolate (WP) was converted into aerogel particles via supercritical CO2 drying. Oleogels were then prepared by absorption of sunflower (SO) or flaxseed (FLX) oil (80%, w/w) into the aerogel particle template and subjected to in vitro digestion. WP aerogel-templated oleogels showed a specific destructuring behaviour during digestion. Confocal micrographs clearly demonstrated that the original oleogel structure was lost at the gastric level, with the release of oil droplets smaller ( D 32 < 10 μm) than those observed in the case of the unstructured oils ( D 32 > 30 μm), stabilised by undigested aerogel proteins. Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) and bicinchoninic acid (BCA) assay confirmed that aerogelation reduced the gastric proteolysis of WP from nearly 100% to 70%. The digestion of the SO oleogel led to similar gastric protein digestibility. In contrast, in the case of the FLX oleogel, gastric proteolysis decreased to 40%, suggesting a role of the oil nature in steering WP aerogel digestion. In all cases, upon intestinal digestion aerogel proteins resulted completely hydrolysed. The lipolysis degree of SO (75%) and FLX (34%) oil in the oleogels was higher than that of the unstructured SO (66%) and FLX (24%) oils, due to the larger surface offered by smaller oil droplets to the action of intestinal lipases. This was confirmed by dynamic light scattering, showing a shift towards smaller size in the digestive micelle distribution of oleogels at the end of the intestinal phase. Oleogelation through the WP aerogel-template approach could be regarded as a strategy to steer lipid digestibility while also modulating the release of bioaccessible peptides.